The trascendentality of personal knowledge - Sellés, Juan Fernando (Pensamiento. Revista de Investigación e Información Filosófica, 2016)
This article talks about the distinction between actus essendi and essentia in the human being. It contends that the human person is the act of being, and that natura and human essentia depend on the human person. It maintains that the human person is composed of pure and intimate perfections called «trascendentals», one of which is personal knowledge (intellectus agens) that can be united and converted with others (coexistentia, liberty, and personal love). It indicates that this personal knowledge is achieved through the habit of wisdom. It also indicates the theme of this personal knowledge, i.e., God.